Comparison of the Performance of a Novel, Smartphone-based, Head-mounted Perimeter (GearVision) With the Humphrey Field Analyzer. Issue 4 (April 2021) - Pradhan, Zia S.; Sircar, Tushar; Agrawal, Harshit; Rao, Harsha L.; Bopardikar, Ajit; Devi, Sathi; Tiwari, Vijay N.
Abstract : Precis: The agreement between a head-mounted perimeter [GearVision (GV)] and Humphrey field analyzer (HFA) for total threshold sensitivity was a mean difference of −1.9 dB (95% limits of agreement −5 to 1). GV was the preferred perimeter in 68.2% of participants. Purpose: The purpose of this study was to compare reliability indices and threshold sensitivities obtained using a novel, smartphone-based, head-mounted perimeter (GV) with the HFA in normal, glaucoma suspect and glaucoma patients. A secondary objective was to evaluate the subjective experience participants had with both perimeters using a questionnaire. Methods: In a prospective, cross-sectional study; 107 eyes (34 glaucoma, 18 glaucoma suspect, and 55 normal) of 54 participants underwent HFA and GV in random order. The main outcome measure was the agreement of threshold sensitivities using Bland and Altman analysis. Participants also completed a questionnaire about their experience with the devices. Results: Median false-positive response rate for GV was 7% (4% to 12%), while for HFA it was 0% (0% to 6%, P <0.001). Median false-negative response rate was similar for both tests. In all, 84 eyes with reliable HFA and GV results were included in the final analysis. Median threshold sensitivity of all 52 points on HFA was 29.1 dB (26.5 to 30.7 dB) and for GV was 30.6 dB (29.1 to 32.6 dB; P <0.001). Mean difference (95% limits of agreement) in total threshold sensitivity between HFA and GV was −1.9 dB (−5 to 1 dB). The 95% limits of agreement were fairly narrow (−8 to 2 dB) across the 6 Garway-Heath sectors. Most participants preferred to perform GV (68.2%) if required to repeat perimetry compared with HFA (20.6%, P <0.001). Conclusions: There was fairly good agreement between the threshold sensitivities of GV and HFA. GV was also preferred by most patients and could potentially supplement HFA as a portable or home perimeter. Abstract : Supplemental Digital Content is available in the text.